The decanting of acid mine water in the Gauteng City-Region: analysis, prognosis and solutions - McCarthy, Terence (My University, 2010)
The large void beneath the Witwatersrand created by gold mining over the last 120 years is filling with water, which is rising at about 15m per month. The void will fill and water will begin to leak out (decant) on surface in about three years from now. It is likely that multiple decant points will develop in municipal areas across the Witwatersrand from Roodepoort to Boksburg. experience on the West Rand has shown that the quality of the water is likely to be poor and toxic. The prime risk area where decant points are likely to develop is in a zone about 500m wide straddling Main Reef Road and the M2 motorway, plus a secondary zone some two kilometres to the south. deep basements of buildings and other sub-surface infrastructure in the risk zones could experience flooding and the underground facility at Gold Reef City, a national treasure, will be lost. The problem can be solved by establishing pump stations at shallow depth in the mining belt to keep the water at a safe depth below surface. a depth of 300m is recommended in order to protect the Gold Reef City facility. The technological capability to do this is readily available, and the necessary water treatment processes are well established. although initially expensive, the pumping operation may ultimately generate a profit. Moreover, the cost of not pumping may ultimately vastly exceed the cost of timely intervention. establishing the necessary pumping and water treatment infrastructure will take considerable time, and therefore immediate action is required.
September 2010
Keywords: decanting acid mine water, Gauteng city-region; decanting of acid mine water, Gauteng city-region